Right atrial myxoma at Muhimbili National Hospital: a case report (Tanzania Medical Journal, 2010)
Background: Primary cardiac neoplasms are rare most of them are benign. Cardiac myxomas are the commonest benign lesion and the initial presentation may be accompanied with pulmonary, cerebral or systemic complications. Complete resection of the tumour is associated with good prognosis but recurrence is a frequent post operative complication. We report a first rare case from our centre of right atrial myxoma occurring in a young lady of 20 years old, a diagnosis and technique of resection is also explained. Case presentation: We report a rare case of a young girl who had presented to us with history of shortness of breath and easy fatigability, she was also found to have features of both upper andlower cava hypertension and was in NYHA class IV. The 2-D echocardiography revealed a right atrial tumor encroaching the tricuspid valve, chest radiography showed gross cardiomegally and right lower lung collapse. A clinical diagnosis of right atrial tumour was reached. The patient was scheduled to undergo open heart surgery and tumour resection on 23rd September 2009 and was prepared accordingly. A classical median sternotomy followed by major vessel cannulation in which the cava were cannulated distally. Patient was cooled to 22 centigrade the tumour was found filling the whole of right atrium cavity, friable with a broad stalk on the right atrial appendage extending and infiltrating the crista terminalis. It was excised and tissue was taken for histopathology. The right atrium was reconstructed and closed with adequate size of atrium. The histopathology revealed a typical right atrial myxoma. Postoperatively the patient developed massive right sided pleural effusion that was managed by tube thoracostomy. Eventually the patient recovered and was discharged to be followed at outpatient clinic. Conclusion: Right atrial myxomas are rare lesion occurring in 5- 10% of all cases of cardiac myxoma. The peak incidence is between 3rd to 6th decades of life. Our case was unusual as it occurred in the 2nd decade and in the right atrium with multicentric origin though still confined in the right atrium. She also presented with pulmonary complication of right sided lung collapse. Early diagnosis andresection is followed by good prognosis and recurrence rate is low. Resection was done and the postoperative period was uneventful.Keywords: cardiac myxoma, atrial tumour, cardiac tumour, multicentric, subendocardium, mesechymal tissue